Particle image velocimetry analysis of a swirling bed operation by using a mesh-coupled annular air distributor - Naz, M.Y. (Springer Verlag, 2019)
An air distributor is regarded as a key component of swirling fluidized bed designs. It considerably affects the quality of fluidization and efficiency of a swirling fluidized bed (SFB). In this study, a velocimetry technique was used to evaluate the performance of the SFB design operated with a mesh-coupled annular blade air distributor. The MATLAB-based particle image velocimetry (PIV) was carried out from top and side of the swirling bed. The velocity vector fields and average velocities of the fluidized particles at different points across the bed flow were determined by changing the particles size, particle density and superficial air velocity (SAV). PIV analysis revealed that the particles in a fluidized bed form a partially differentiable layer. The partially segregated bed layers included a thin layer of fast-moving particles near the distributor, a thick layer at the center and a slight bubbling top layer. It was noted that with an increase in SAV, the average particle velocity also increases. However, the particle velocity depreciates in moving upward along the bed column. Â© 2019, The Brazilian Society of Mechanical Sciences and Engineering.